2016
DOI: 10.15376/biores.11.4.9112-9125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diffusive Impregnation of Birch Veneers with Fire Retardant on Plywood Properties

Abstract: Wood is a natural, organic material that cannot be exposed to high temperatures, fire, or heat, especially when wood or wood-based materials are used as construction elements. The fire-extinguishing composition of di-ammonium phosphate, ammonium sulfate, and ammonium bromide (DAB) was used to increase the fire-resistance of birch plywood. The effects of various parameters of diffusive impregnation of the veneer (temperature and concentration of impregnating solution, duration of impregnation) were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This technology has several benefits comparing to surface treatment and high-pressure treatment of ready-made birch plywood. Distribution of fire protective chemicals in cross-section of plywood in this case should be very even (Bryn et al, 2016;Bekhta et al, 2016). Architects, design engineers, builders and others must be aware of the potential problems of using FRT wood in severe environments.…”
Section: Impact Of High-pressure Impregnation and Fire Protective Coatings On The Reactionmentioning
confidence: 98%
See 1 more Smart Citation
“…This technology has several benefits comparing to surface treatment and high-pressure treatment of ready-made birch plywood. Distribution of fire protective chemicals in cross-section of plywood in this case should be very even (Bryn et al, 2016;Bekhta et al, 2016). Architects, design engineers, builders and others must be aware of the potential problems of using FRT wood in severe environments.…”
Section: Impact Of High-pressure Impregnation and Fire Protective Coatings On The Reactionmentioning
confidence: 98%
“…High pressure impregnation with fire retardants becomes an interesting option for improvement of plywood overall performance in fire (Seo, Hwang, Lee, 2017). Bryn et al (2016) has performed diffusive impregnation of birch veneer and got good fire-Risk matrix for milk production and processing in Latvia during the COVID-19 pandemic Bekhta et al (2016) showed that increased moisture content has a positive impact on the diffusive impregnation process and can be a factor in reducing the duration of impregnation. Deeper knowledge in the field of diffusive impregnation of birch veneer with different fire-retardant chemical is needed to develop maximal fire performance birch plywood.…”
Section: Impact Of High-pressure Impregnation and Fire Protective Coatings On The Reactionmentioning
confidence: 99%
“…To achieve these qualities, it is necessary to implement fire protection, for example, by treating the particles using fire retardants [ 28 ]. It protects the material throughout its entire cross-section, not only on the surface as in the case of fire-resistant coating application [ 29 , 30 ]. However, the impregnating solutions can not only influence the curing process of adhesives but also change the condition of the wood surface.…”
Section: Introductionmentioning
confidence: 99%